Neuroplasticity of pain processing and motor control in CAI patients: A UK Biobank study with clinical validation - Wang, Yiran; Li, Qianru; Xue, Xiao'ao; Xu, Xiaoyun; Tao, Weichu; Liu, Sixu; Li, Yunyi; Wang, He; Hua, Yinghui (Frontiers in Molecular Neuroscience, 2023)
Background Pain plays an important role in chronic ankle instability (CAI), and prolonged pain may be associated with ankle dysfunction and abnormal neuroplasticity. Purpose To investigate the differences in resting-state functional connectivity among the pain-related brain regions and the ankle motor-related brain regions between healthy controls and patients with CAI, and explore the relationship between patients' motor function and pain. Study design A cross-database, cross-sectional study. Methods This study included a UK Biobank dataset of 28 patients with ankle pain and 109 healthy controls and a validation dataset of 15 patients with CAI and 15 healthy controls. All participants underwent resting-state functional magnetic resonance imaging scanning, and the functional connectivity (FC) among the pain-related brain regions and the ankle motor-related brain regions were calculated and compared between groups. The correlations between the potentially different functional connectivity and the clinical questionnaires were also explored in patients with CAI. Results The functional connection between the cingulate motor area and insula significantly differed between groups in both the UK Biobank (p = 0.005) and clinical validation dataset (p = 0.049), which was also significantly correlated with Tegner scores (r = 0.532, p = 0.041) in patients with CAI. Conclusion A reduced functional connection between the cingulate motor area and the insula was present in patients with CAI, which was also directly correlated with reduction in the level of patient physical activity.